Hepatitis B management during immunosuppression for haematological and solid organ malignancies: an Australian consensus statement. Issue 10 (19th May 2019) - Doyle, Joseph; Raggatt, Michelle; Slavin, Monica; McLachlan, Sue‐Anne; Strasser, Simone I; Sasadeusz, Joseph J; Howell, Jessica; Hajkowicz, Krispin; Nandurkar, Harshal; Johnston, Anna; Bak, Narin; Thompson, Alexander J
Abstract: Introduction: Individuals with chronic hepatitis B virus (HBV) infection or past exposure to HBV infection have a substantial risk of reactivation during immunosuppressive cancer therapy. HBV reactivation can lead to liver failure, cancer treatment interruption or death. Clinical concordance with screening and treatment guidelines is inconsistent in practice, and existing international guidelines are not specific to the Australian context. We developed an Australian consensus statement with infectious diseases, hepatology, haematology and oncology specialists to inform hepatitis B screening and antiviral management for immunocompromised patients with haematological and solid organ malignancies in Australia. Main recommendations: Recommendations address four key areas of HBV infection management for immunocompromised patients with haematological and solid organ malignancies: who to test for HBV infection, when to start antiviral agents, when to stop antiviral agents, and how to monitor patients during cancer therapy. We recommend testing all patients undergoing cancer treatment for hepatitis B (including HBV surface antigen [HBsAg], HBV core antibody [anti‐HBc], and HBV surface antibody) before cancer treatment. Individuals with chronic HBV infection (HBsAg positive) or past exposure (HBsAg negative and anti‐HBc positive) receiving higher risk chemotherapy require antiviral prophylaxis using entecavir or tenofovir. Changes in management as a result of this statement: This consensus statement will simplify the approach to testing and prophylaxis for HBV infection during cancer therapy, and harmonise approaches to discontinuing and monitoring individuals which have been highly variable in practice. We advocate for broader Medicare Benefits Schedule and Pharmaceutical Benefits Scheme access to HBV testing and treatment for patients undergoing cancer therapy.